Humic acid-mediated activation of antimony colloid during soil redox cycles: Mechanisms and environmental implications - Xiongkai Zheng; Jiaming Xu; Haiming Cai; Qiming Mo; Yihao Li; Qixian Fu; Lijuan Zeng; Yongyang Wang; Xueqin Tao; Zhi Dang; Guining Lu (Journal of Hazardous Materials, 2026)

A multimodal prediction model for brain hematoma expansion based on deep neural network with transformer-driven collaborative attention fusion - Nanxu Tao; Jianping Chen; Hongjie Wu; Jiaqi Dai; Tao Zhong; Chenyang Song; Ye Wang; Yanming Chen; Qiming Fu (Medical & Biological Engineering & Computing, 2026)

Dependencies of ecological drought on climatic drivers in diverse ecosystems: Implications for water resources management - Zhiwen You; Leying Fu; Huaiwei Sun; Xuan Ban; Yubo Li; Pengsheng Li; Qiming Zheng; Changqing Meng; Jie Xue; Hui Qin (Journal of Environmental Management, 2026)

Non-invasive early sex identification of hybrid sturgeon (Huso dauricus♀ × Acipenser schrenckii♂) based on multi-view images - He Gao; Qiaokun Liu; Xiao Chen; Rongzhu Zhou; Shanzhong Zhang; Junting Li; Yinhua Zhou; Suxing Fu; Chengjiang He; Tonghan Wu; Siyu Duan; Jia Xu; et al. (Aquaculture, 2026)

Graph-based visual analysis for HVAC system anomaly detection - Tianyuan Cao; Yunzhe Wang; Qiming Fu; You Lu; Jianping Chen; Yushi Li; Chengtao Ji (Energy and Buildings, 2026)

Automated measurement of optic nerve sheath diameter using ocular ultrasound video - Renxing Li; Weiyi Tang; Peiqi Li; Qiming Huang; Jiayuan She; Shengkai Li; Haoran Xu; Yeyun Wan; Jing Liu; Hailong Fu; Xiang Li; Jiangang Chen (Medical & Biological Engineering & Computing, 2026)

Explore the relationship between Bowen ratio and evapotranspiration in wetlands using the maximum entropy production model - Huaiwei Sun; Leying Fu; Weiguang Wang; Jie Xue; Jing Wang; Weihong Liao; Haicheng Li; Xunlai Sun; Yong Yang; Jingfeng Wang; Hong Zhang; Fulong Chen; et al. (Journal of Hydrology, 2025)

Enabling high-performance aqueous Zn batteries with sub-zero temperatures surpassing room temperature combining cosolvent engineering and redox regulation strategy - Qiong Li; Ganghui Wei; Ni Lan; Yanzheng Li; Libo Wang; Xinyu Zhang; Yujun Fu; Qiming Liu; Yonggang Zhao; Deyan He (Chemical Engineering Journal, 2025)

Electronic structure regulation inducing multicationic redox behavior toward NASICON-cathode for sodium-ion batteries - Han Su; Yangbin Fu; Huijuan Zhu; Kai Wang; Jie Wang; Xuanzhang Chen; Qiming Liu (Chemical Engineering Journal, 2025)

Analysis of Morphological Characteristics of Male and Female Gymnocypris eckloni Herzenstein - Qiming Wang; Suxing Fu; Xiaoyi Chen; Yuting Duan; Luo Lei; Yawen Fan; Chaowei Zhou (Fishes, 2025)
Accurate sex identification is crucial for the artificial breeding of fish species, and identification based on phenotypic traits is the preferred method owing to its low cost and rapidity. This study aimed to investigate morphological differences between male and female Gymnocypris eckloni Herzenstein. A total of 166 G. eckloni individuals (83 males and 83 females) were included, and 20 morphological indicators, including head length, snout length, and body weight, were measured. Various analytical methods, such as correlation analysis, principal component analysis, discriminant analysis, and systematic cluster analysis, were used to compare the morphological characteristics of male and female G. eckloni. The result showed significant differences in morphological characteristics between male and female individuals (p ≤ 0.05). Principal component analysis revealed five main components that collectively contributed to 83.64% of the variance, primarily including body length, fork length, total length, and body weight, highlighting the significance of these components in sex differentiation. Subsequently, a mathematical model was constructed via discriminant analysis. This model demonstrated an accuracy of 79.5% and 73.5% in identifying male and female G. eckloni, respectively, with an overall accuracy of 76.50%. Furthermore, on analyzing the relationship between body length and body weight in G. eckloni, we found differences in growth patterns between sexes. In particular, female fish usually weighed more than male fish, which was consistent with the biological characteristics and energy distribution patterns of G. eckloni. These results suggest that sexual dimorphism in G. eckloni is primarily concentrated in body shape and head morphology, which provides a reliable basis for sex identification based on morphological differences.

Understanding the nutritional benefits through plant proteins-probiotics interactions: mechanisms, challenges, and perspectives - Qiming Wu; Juntao Kan; Zhengying Cui; Yuchen Ma; Xin Liu; Ruifang Dong; Dejian Huang; Lin Chen; Jun Du; Caili Fu (Critical Reviews in Food Science and Nutrition, 2025)

Decoding the intestinal response to heat stress in Gymnocypris eckloni: Insights from a thorough analysis of microbiome and transcriptome - Chaowei Zhou; Yuting Duan; Junting Li; Suxing Fu; Shuhao Bai; Yutong Zhuang; Hejiao Li; Yinhua Zhou; Jian Shen; Rongpan Zhou; Fan Yang; Zhichao Liu; et al. (Aquaculture, 2024)

Female urinary incontinence in China after 15 years’ efforts: Results from large-scale nationwide surveys - Jiming Zhu; Haiyu Pang; Peicheng Wang; Yanhua Chen; Huihui Li; Qing Liu; Luwen Wang; Hangmei Jin; Liyan Gong; Jingyan Xie; Ting Lai; Aiyang Li; et al. (Science Bulletin, 2024)

Unlocking the power of activated carbon-mediated peracetic acid activation for efficient antibiotics abatement in groundwater: Coupling the processes of electron transfer, radical production, and adsorption - Si Li; Chaomeng Dai; Jixiang Li; Yanping Duan; Rongbing Fu; Yalei Zhang; Jiajun Hu; Lang Zhou; Luochao Wan; Qiming Zhang; Zhibo Zhang (Journal of Hazardous Materials, 2024)

Spatiotemporally continuous PM2.5 dataset in the Mekong River Basin from 2015 to 2022 using a stacking model - Debao Chen; Xingfa Gu; Hong Guo; Tianhai Cheng; Jian Yang; Yulin Zhan; Qiming Fu (Science of The Total Environment, 2024)

ED-DQN: An event-driven deep reinforcement learning control method for multi-zone residential buildings - Qiming Fu; Zhu Li; Zhengkai Ding; Jianping Chen; Jun Luo; Yunzhe Wang; You Lu (Building and Environment, 2023)

Exploitation of the antifungal and antibiofilm activities of plumbagin against Cryptococcus neoformans - Weidong Qian; Wenjing Wang; Jianing Zhang; Yuting Fu; Qiming Liu; Xinchen Li; Ting Wang; Qian Zhang (Biofouling, 2022)

Overview of SARS-CoV-2 genome-encoded proteins - Chongzhi Bai; Qiming Zhong; George Fu Gao (Science China Life Sciences, 2022)

Comparison of gene co-networks reveals the molecular mechanisms of the rice (Oryza sativa L.) response to Rhizoctonia solani AG1 IA infection - Jinfeng Zhang; Wenjuan Zhao; Rong Fu; Chenglin Fu; Lingxia Wang; Huainian Liu; Shuangcheng Li; Qiming Deng; Shiquan Wang; Jun Zhu; Yueyang Liang; Ping Li; et al. (Functional & Integrative Genomics, 2018)